Smart grid infrastructure & networking - Iniewski, Krzysztof (McGraw-Hill, 2013)
A complete guide to smart grid networking and communications for energy engineers with contributions from more than 30 experts, Smart Grid Infrastructure & Networking describes cutting-edge technologies for connecting the electrical power infrastructure to modern, computerized communications networks. The book offers essential information on standardization, applications, protocols, automation, architecture, and management. Key topics such as bidirectional communication, automation, renewable energy integration, wireless sensor networks, and more are discussed in this practical, comprehensive resource. Coverage includes: Demand-side energy management * The modernization of distribution automation featuring intelligent FDIR and volt-var optimization Advanced asset management * Wide-area early warning systems * The integration of renewable energy sources into smart grids * The microgrid in the electric system transformation * Enhancing the integration of renewables in radial distribution networks through smart links * Voltage-based control of DG units and active loads in smart microgrids * Electric vehicles in a smart grid environment * Low-voltage, DC grid-powered LED lighting system with smart ambient sensor control for energy conservation in green building * Multiple distributed smart microgrids with a self-autonomous, energy harvesting wireless sensor network * Wireless sensor networks for consumer applications in the smart grid * ZigBee-based wireless monitoring and control system for smart grids.